Wettability of pear leaves from three regions characterized at different stages after flowering using the OWRK method. Issue 8 (15th March 2018) - Gao, Yue; Guo, Ruifeng; Fan, Renjun; Liu, Zhongfang; Kong, Weina; Zhang, Pengjiu; Du, Feng‐pei
Abstract: BACKGROUND: A better understanding of leaf surface wettability is critical to improve the adhesion of liquid pesticides. Leaf surface wettability is dependent on the property of the liquid as well as the physical and chemical properties of the leaf, which vary with climate and growth stage. The aim of this study was to characterize the wettability of pear leaves from three different climatic regions at different stages after flowering. RESULTS: The contact angles of different test liquids were measured on both adaxial and abaxial pear leaf surfaces and the Owens–Wendt–Rabel–Kaelble (OWRK) method was used to calculate surface free energy (SFE) and its polar and non‐polar components. The results demonstrated that the SFE of both the adaxial and abaxial surface of the pear leaf, and the proportion of polar component, increased with increasing time after flowering. At early growth stages, pear leaves were highly hydrophobic, similar to a polytetrafluoroethylene surface, whereas at later growth stages, pear leaves were hydrophobic, more similar to a polymethylmethacrylate surface. Also, the SFE differed with climatic region. Factors influencing these changes are discussed. CONCLUSION: Changes in contact angles and SFE correlated with the change of the leaf surface wettability. Leaves became easier to wet (higher SFE), with an overall increasing polar component to the surface, with increasing age after flowering. As expected, changes in wettability were found in pear leaves at different stages after flowering and in different regions ( P  < 0.05). Pear leaves from Yuanping were easier to wet than leaves from Yuci and Linyi, and adaxial surfaces were easier to wet than abaxial surfaces. These results provide beneficial information for the application of agrochemicals for improved wetting and spreading behavior. © 2018 Society of Chemical Industry Abstract : A better understanding of pear leaf surface wettability is critical to improve the adhesion of liquid pesticides. This article provides beneficial information for the application of agrochemicals for improved wetting and spreading behavior.